2017
DOI: 10.1177/1558944717735943
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Upper Extremity Injuries Presenting to US Emergency Departments

Abstract: Soft tissue contusion was the most frequent diagnosis. More than half of the patients were male, while the majority of patients were under the age of 44. Ninety-three percent of patients did not require hospital admission. Half had private insurance and the two-thirds of these patients were seen at nonteaching facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 15 publications
4
28
0
Order By: Relevance
“…Pichard et al report that the proximal or distal location of upper extremity problem did not differ between 2019 and 2020 [14] . Similar trends for the type of hand and wrist injuries have been demonstrated in several studies [ 6 , 7 , 15 , 16 ], with the exception of a study focusing on the effect of the recent pandemic on hand and wrist injuries, with skeletal injuries being the second reason for ED visits, following lacerations [14] . Due to surgical treatment and prolonged rehabilitation, over 75% of health care costs are attributed to fractures [7] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Pichard et al report that the proximal or distal location of upper extremity problem did not differ between 2019 and 2020 [14] . Similar trends for the type of hand and wrist injuries have been demonstrated in several studies [ 6 , 7 , 15 , 16 ], with the exception of a study focusing on the effect of the recent pandemic on hand and wrist injuries, with skeletal injuries being the second reason for ED visits, following lacerations [14] . Due to surgical treatment and prolonged rehabilitation, over 75% of health care costs are attributed to fractures [7] .…”
Section: Discussionsupporting
confidence: 80%
“…Due to surgical treatment and prolonged rehabilitation, over 75% of health care costs are attributed to fractures [7] . Infection rates remained low and very similar between 2019 and 2020 in our study, although they have been reported to be as high as 17% [16] .…”
Section: Discussionsupporting
confidence: 73%
“…Traumatic peripheral nerve injuries are common and caused by factors ranging from acts of violence, motor vehicle accidents, and recreational activities, to iatrogenic injuries during surgery. The majority of nerve injuries occur in the upper extremity . It is estimated that 1‐3% of all upper extremity trauma patients are diagnosed with nerve injuries during the first few months after trauma .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of human nerve injuries, resulting from vehicle accidents, recreational activities and iatrogenic injuries during surgeries, occur in the upper extremity ( Figure 3 A) [ 42 ]. Seminal studies in rodents in the Gordon and Brushart laboratories with Canadian and German collaborators [ 29 , 43 , 44 , 45 , 46 , 47 ] (reviews [ 33 , 48 , 49 , 50 , 51 , 52 ]), and in human patients in the Chan laboratory in Canada [ 53 , 54 , 55 ] (reviews [ 33 , 48 , 52 , 56 ]), demonstrated that brief low frequency, electrical stimulation of the nerve proximal to the site of transection and surgical repair, accelerated motor and sensory nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%